TRASTUZUMAB IN METASTATIC BREAST CANCER: SYSTEMATIC REVIEW OF COST-EFFECTIVENESS ANALYSES - Andrade, Thays Santos De; Mosegui, Gabriela Bittencourt Gonzalez; Miranda, Elaine Silva; Vianna, Cid Manso De Mello; De Souza, Tayna Felicissimo Gomes; Rodrigues, Marcus Paulo Da Silva (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: To conduct a systematic review of cost-effectiveness analyses of trastuzumab in patients with metastatic breast cancer overexpressing human epidermal growth factor receptor 2. Methods: A systematic review for the years 1998 to 2013 was conducted. A survey of the scientific literature was performed using six electronic databases, two search tools on the internet and a manual search of references using search strategies for each database. The selected studies were assessed for quality according to specific methodology. Data analysis was performed by converting the costs and by observations made from the incremental cost-effectiveness ratios of trastuzumab. Results: From a detailed analysis of 521 retrieved articles, 13 articles were selected for this review. The treatment regimens adopted for cost-effectiveness were varied. Eight studies compared treatment with trastuzumab as first line for metastatic disease, and five studies compared treatment with trastuzumab as the second line. All the studies were using trastuzumab as second-line treatment was not considered a cost-effective intervention. The analyses used different thresholds to determine whether treatment with trastuzumab was cost-effective as well as to determine differences in modeling costs, outcomes and treatment patterns. Conclusion: The use of trastuzumab, alone or combined, was cost-effective as first-line treatment. Differences were found in the quality of the included studies. Conducting new cost-effectiveness analyses of trastuzumab in metastatic breast cancer is required, in alliance with political, social and administrative factors, to help decision makers concerning its incorporation.